FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA BANK (STUDI EMPIRIK PADA INDUSTRI PERBANKAN DI BURSA EFEK INDONESIA) - Didik Purwoko; Bambang Sudiyatno (Jurnal Bisnis dan Ekonomi, 2013)
This study aims to examine the factors that affect the performance of banks listed on the Indonesia Stock Exchange. These factors were operating efficiency (ROA), credit risk (NPL), market risk (NIM), capital (CAR), and liquidity (LDR). The data used in this study were obtained from the Company's Financial Statements Banking Publications listed on the Stock Exchange. Based on purposive sampling method, the sample is worth using as many as 28 corporate banking with the following criteria: banking company is listed on the Indonesia Stock Exchange (BEI), never on delete, and provide financial statement data for the period 2007-2010. The type of data used are secondary data, which is a combination of time series and cross section data. Technical analysis used multiple linear regression. The results showed that the variables BOPO and NPL are significant negative effect on ROA, NIM is significant positive effect on ROA, CAR and LDR whereas no significant effect on ROA. Coefficient of determination, which shows the magnitude of the influence BOPO, NPL, NIM, CAR and LDR to ROA are 73.1%, while the rest of 26.9% explained by other causes outside the model. Key words: efficiency of operations (ROA), credit risk (NPL), market risk (NIM), capital (CAR), liquidity (LDR).